STATE RESPONSIBILITY FOR THE FULFILLMENT OF MEDICAL EXPENSES FOR VICTIMS OF KLITIH CRIME YOGYAKARTA - Arabella, Cecilia; Hidayat, Rizkiana; Tandori, Tandori; Sundari, Elisabeth (Jurnal Meta-Yuridis, 2025)
The research aims to examine the state's responsibility in fulfilling health costs for victims of street crime in D.I Yogyakarta based on the 1945 Constitution and Presidential Regulation No. 82/2018 excluding the provision of health insurance for victims of klitih crime violence. The research method used is normative juridical with the framework of Pancasila welfare state theory, which focuses on analyzing legal norms and public policies. This research confirms the discrimination between existing policies and the principle of state responsibility in fulfilling health rights for victims. Current policies have not fully met constitutional standards in providing health protection to victims of violent crimes, which has the potential to hinder their rehabilitation process. Most victims face challenges in accessing health services due to lack of coverage. Therefore, comprehensive policy reforms are needed to strengthen social protection, by optimizing inter-agency cooperation, and ensuring fair and equitable accessibility of health services for all victims of criminal acts.